Ideational Leadership in German Welfare State Reform How Politicians and Policy Ideas Transform Resilient Institutions - Stiller, Sabina (Changing Welfare States, 2009)
The author of this innovative study argues that key politicians and their policy ideas, through "ideational leadership", have played an important role in the passing of structural reforms in the change-resistant German welfare state. This argument is based on in-depth case studies of individual reforms in health care, pensions and unemployment insurance since the early 1990s as well as a concise analysis of recent changes in family policy. Stiller concludes that Germany, traditionally a Bismarckian welfare state, has embarked on a path of 'hybridisation' that confronts German politics with growing societal divisions. This thought-provoking title is highly recommended for policymakers, scholars and students interested in the past and future reforms of the German welfare state, leadership, and the role of ideas in policymaking.